2015
DOI: 10.1177/000313481508100117
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Suture Can Accelerate Wound Healing of Lower Midline Incision: A Randomized Controlled Trial

Abstract: Poor wound healing is one of the most common complications after laparotomy, especially in lower abdominal midline incisions. The aims of this trial are to assess the value of subcutaneous suture and identify risk factors to prevent poor wound healing. From October 2010 to October 2011, a total of 180 patients were randomized to the subcutaneous suture group (n = 89) or control group (n = 91) after laparotomy with a lower midline incision. Univariate and multivariate analyses were performed to determine the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Otherwise, as an European retrospective cohort study suggested[8], compared with non-AWD cases, patients with AWD had a higher in-hospital case fatality over 7.5%, longer average hospital stay over 15.6 days and extra additional fees for €14327. Since then there has been amounts of research about abdominal incision dehiscence in adults [9][10][11], only a few studies related to children's, let alone that of newborns. Apart from the speci c pathophysiological and anatomical characteristics of neonates, compared with children and adults, disease progress changes in a more rapid way and situation of abdominal wound rupture is more complex, leading to more depressed consequences in newborns [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, as an European retrospective cohort study suggested[8], compared with non-AWD cases, patients with AWD had a higher in-hospital case fatality over 7.5%, longer average hospital stay over 15.6 days and extra additional fees for €14327. Since then there has been amounts of research about abdominal incision dehiscence in adults [9][10][11], only a few studies related to children's, let alone that of newborns. Apart from the speci c pathophysiological and anatomical characteristics of neonates, compared with children and adults, disease progress changes in a more rapid way and situation of abdominal wound rupture is more complex, leading to more depressed consequences in newborns [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%